A framework for evaluating the public health impact of e‐cigarettes and other vaporized nicotine products. (25th April 2016) - Levy, David T.; Cummings, K. Michael; Villanti, Andrea C.; Niaura, Ray; Abrams, David B.; Fong, Geoffrey T.; Borland, Ron
Abstract: The use of vaporized nicotine products (VNPs), especially e‐cigarettes and, to a lesser extent, pressurized aerosol nicotine products and heat‐not‐burn tobacco products, are being adopted increasingly as an alternative to smoking combusted products, primarily cigarettes. Considerable controversy has accompanied their marketing and use. We propose a framework that describes and incorporates patterns of VNP and combustible cigarette use in determining the total amount of toxic exposure effects on population health. We begin by considering toxicity and the outcomes relevant to population health. We then present the framework and define different measures of VNP use; namely, trial and long‐term use for exclusive cigarette smokers, exclusive VNP and dual (cigarette and VNP) use. Using a systems thinking framework and decision theory we considered potential pathways for current, former and never users of VNPs. We then consider the evidence to date and the probable impacts of VNP use on public health, the potential effects of different policy approaches and the possible influence of the tobacco industry on VNP and cigarette use.